Exploring factors that motivate nursing students to engage in skills practice in a laboratory setting: A descriptive qualitative design - Yoko Nakayoshi; Miyuki Takase; Mayumi Niitani; Takiko Imai; Mari Okada; Kumiko Yamamoto; Yuri Takei (Elsevier, 2021)
Objectives: The aim of this study was to explore factors that motivate students to engage in skills practice in a laboratory setting, and to identify their motivation types and the regulatory styles. Methods: Semi-structured interviews were conducted with 23 nursing students from three universities between November 2017 and January 2018. A thematic analysis was used to identify factors associated with students' motivation to engage in skills practice in a laboratory. The types and the regulatory styles of student motivation were identified based on the self-determination theory. Results: Seven motivating factors were identified. These factors included the students' desire "to acquire the skills necessary to work as a nurse", the "desire to improve skills in preparation for clinical practicum", and their felt "obligations to patients as a nurse". Moreover, "the impetus to study arising from the objective evaluation of oneself and others" and "wanting to pass the skills examination" motivated the students to engage in skills practice. A "learning environment that facilitates students' learning" and the "supportive involvement of educators" facilitated their learning. Based on the self-determination theory, the students were found to embrace extrinsic motivation with four regulatory styles of motivation, namely integrated, identified, introjected, and external regulation. Conclusions: Nurse educators should understand the motivating factors of students, and help students embrace a more internally controlled motivation by helping them envision their future careers as nurses, and by fostering their ethical duty to care for patients.